The impact of a gluten-free diet on the growth pattern of Saudi children with celiac disease - Omar Ibrahim Saadah (Journal of the Pakistan Medical Association, 2021)
Objective: To describe the growth pattern of children with celiac disease (CD) after introduction of a gluten-free diet (GFD). Methods: In this retrospective, children 2–16 years old with biopsy-proven CD in 2015–2018 were included in the study conducted at King Abdulaziz University Hospital, Jeddah, Saudi Arabia. Serial measurements of height-for-age z-score (HAZ) and weight-for-age z-score (WAZ), were recorded at 0, 4, 8, 12, and 16 months. Data on insulin-like growth hormone-1 (IGF-1) and insulin-like growth factor binding protein-3 (IGFBP-3) obtained at diagnosis and during follow-up were retrieved. Clinical, demographic, and laboratory data were extracted from patients’ medical files. Results: The median age for the patients was 8.9 years (range, 2.4–16 years). Males constituted 53.2%. The mean WAZ at diagnosis was -2.8±1.9 and the mean HAZ was -3±0.99. Trend analysis indicated a significant time effect for WAZ (p<0.001) and for HAZ (p<0.001). The mean IGF-1 was 133.4±96.8 ng/ml and the mean IGFBP-3 was 3174±1081 ng/ml. There was significant increase in the secretion of IGF-1 (p=0.01) and IGFBP-3 (p=0.004) during the first 8 months of a GFD. Conclusion: The administration of a GFD for Saudi children with CD normalizes their growth parameters within 16 months of follow-up and improves the endogenous secretion of growth factors. Keywords: Celiac disease, growth, child, Continuous...